Access to health care perceived by parents caring for their child at home supported by eHealth-a directed approach introducing aperture - Mia Hylén; Stefan Nilsson; Inger Kristensson-Hallström; Gudrún Kristjánsdóttir; Pernilla Stenström; Rúnar Vilhjálmsson (BMC, 2022)
Abstract Background In recent years a variety of eHealth solutions has been introduced to enhance efficiency and to empower patients, leading to a more accessible and equitable health care system. Within pediatric care eHealth has been advocated to reduce emergency and hospital outpatient visits, with many parents preferring eHealth to physical visits following the transition from hospital to home. Still, not many studies have focused on access from the parental perspective. Therefore, the aim of the study was to analyze access to health care as perceived by parents when caring for their child at home, with conventional care supported by eHealth following pediatric surgery or preterm birth. Methods Twenty-five parents who went home with their child following hospitalization and received conventional care supported by eHealth (a tablet) were interviewed in this qualitative study. Directed content analysis was used, guided by a framework for dimensions of access previously described as: approachability, acceptability, affordability, appropriateness, and availability. Results All dimensions of access were present in the material with the dimensions of approachability, appropriateness and acceptability most frequently emphasized. The dimensions highlighted a strong acceptance of eHealth, which was perceived by the parents as beneficial, particularly access to communication with health care personnel familiar to them. The chat function of the tablet was often mentioned as positive. A new dimension was also identified: "aperture." It is defined by the pathways by which communication is transmitted in cyberspace, and these pathways are not easily visualized for parents submitting information, therefore generating concerns. Conclusions Parents generally experienced good access to the eHealth-supported health care. Describing access through its dimensions complemented previous descriptions of eHealth in pediatric care and gave new insights. As such, the new dimension of "aperture", the indeterminate opening of pathways of communication reflecting the uncertainty of not comprehending cyberspace, could be further evaluated. The dimensional framework of access is recommended when evaluating eHealth in the future. Trial registration ClinicalTrials.gov identifier: NCT04150120.